PENGARUH PELATIHAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT WAHANA MAKMUR SEJATI GUNUNG SAHARI, JAKARTA PUSAT - Retno Puji Astuti; Elisabeth Vita (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2019)
In facing the competition and the demands of the work in the current era of globalization, companies are required to have a strategy to always have the ideas or things that could help them getting better, in achieving success. A good company must have a reliable human resource, performermance and able to compete with other companies. Human resources is the most decisive factor in the achievement of the objectives of the company. So companies are expected to provide new knowledge, always with require employees in training programs and provide motivation to employees to have a positive attitude for the sake of achieving a goal corporate and personal. The object of this research is the training, motivation, and performance of employees. The data are collected by disseminating a questionnaire, while sampling using the technique of nonprobability sampling with 50 respondents. Statistics calculation using multiple regression with SPSS software tool 20. The results showed that (1) the training effect significantly to the performance of employees, (2) significant influential motivation on performance of employees.Key words: Training, Motivation, Employee Performance